Supernova archaeoastronomy - Bulhões Martins, Bianca; Ernesto Horvath, Jorge; Sérvulo Maciel Costa, Felipe; Carlos Jafelice, Luiz (Cadernos de Astronomia, 2025)
The historical supernovae, recorded by different observers around the globe for many centuries, may have also been depicted as rock art by Indigenous peoples of the Americas. There are suggestions of the association of petroglyphs and rupestrian art in the northern hemisphere with some of these events. This work aims to present and discuss whether a set of petroglyphs located in the states of Paraíba and Rio Grande do Norte may represent these historical supernovae. Using Stellarium software, the sky patterns at the time of each supernova explosion were simulated and then compared to the figures found. Considering the well-established cultural practices of the Tarairiú peoples, we identified suggestive correspondences between the figures and the supernovae of 185, 1054, and 1572, although the start of a definitive  confirmation depends on dating analysis not yet available.
Keywords: supernova; archaeoastronomy; rock art; Indigenous peoples; Tarairiú